The Impact of the French Colonial Law on the Development of Matrimonial Property Law in Vietnam - NGUYỄN, Linh THỊ MỸ (Díké - Journal of Dezső Márkus Research Group for Comparative Legal History, 2019)
This article analyses the matrimonial property law in Vietnam during the French colonial period. From 1858 to 1954, France invaded Vietnam and applied similar regulations form their homeland to Vietnam. Vietnam has witnessed the term of the matrimonial property law form now onwards. Analysing and understanding the development of the matrimonial property law during French conquest is truly worth researching for Vietnam legal history. This research would be a great idea if it is compared between eastern family regulations and western family ones which were issued during French colonial time. Indeed, the best way to contribute for the improvement of matrimonial property law is to certainly understand its development process.